Riding the logistics wave in China - a study of opportunities, challenges and strategies. - Chan, Min Yu. (2013)
China's logistics industry offers abundant growth opportunities, especially in inland provinces which have been beneficiaries of the boost in domestic consumption over the recent years and will continue to be so in many years to come. The government’s move to open up most parts of the logistics market enables private enterprises to have a share of the burgeoning market. The incumbents are lacking in information technology and knowledge capital relating to logistics. However, the presence of the SOEs creates an unlevelled playing field. Customers also remain mostly cost-conscious, unwilling to pay premium prices for quality services.